(untitled) (Journal of Nobel Medical College, 2020)
Background: Worldwide chronic kidney disease is one of the primary public health problems. This study aimed to find the activity of liver enzymes alanine aminotransferase, aspartate transaminase, alkaline phosphatase, and Gamma-glutamyl transferase in the patient’s serum before and after dialysis in Chronic kidney disease. Materials and Methods: This was a case-control study including 68 cases with chronic kidney disease coming for hemodialysis at dialysis centers and 140 healthy individuals as control. Serum samples were used for the analysis of serum urea and creatinine, liver enzymes aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and gamma-glutamyl transferase using ErbaChem-300 liquid Chemistry autoanalyzer. Pearson’s bivariate correlation analysis and ANOVA were used to correlate variables between the controls and cases. p < 0.05 was considered to be statistically significant. Results: Urea and creatinine levels were significantly higher in both pre and post-hemodialysis as compared to healthy controls with a p-value (p < 0.001). Alanine aminotransferase and aspartate transaminase levels were significantly lower in both pre and post-hemodialysis as compared to healthy controls. On the other hand, serum alkaline phosphatase levels were significantly higher in pre and post hemodialysis as compared to healthy control. Moreover, serum gamma-glutamyl transferase levels were significantly higher in pre and post hemodialysis as compared to healthy control. Conclusion: The study showed differences in the level of liver enzymes in pre and post hemodialysis in chronic kidney disease.